Penggambaran Hari Kiamat dengan Uslub Isti’arah (Metafora) dalam Alquran: Telaah Tafsir Al-Munir - Imroatul Azizah; Ibnu Samsul Huda (Universitas Negeri Malang, 2021)
Abstract: The verse depicting the Day of Judgment uses a lot of comparative language styles, one of which is uslub isti'arah (metaphorical style). This study aims to find verses describing the Day of Judgment with uslub isti'arah in the Qur'an. The research was conducted by analyzing the elements, types, and meanings of uslub isti'arah in the verse. The research design is descriptive qualitative with meaning analysis methods and literature review. Al-Munir's interpretation is used as the main reference in determining the meaning. The results showed that there were 144 verses with two patterns, namely 97 verses mentioning another name for the Day of Judgment according to its occurrence using the word